Are Daojing and Dejing stylistically independent of each other: A stylometric analysis with activity and descriptivity. - Zhou, Haiyan; Jiang, Yue; Wang, Letao (Digital Scholarship in the Humanities, 2023)
It has been qualitatively evidenced that Daojing and Dejing , the two sections of DaoDejing , are independent of each other in content, style, and authorship. However, this claim remains controversial because there has been scant quantitative study of them that probes into their syntactic structure to quantitatively evidence the independence due to methodological challenges to quantitative approaches. To address this problem, the present study employed two indexes of quantitative linguistics, activity and descriptivity, to capture the syntactic features of the inner structure of Daojing and Dejing to validate the independence as of the above. Results of this study reveal that (1) the chi-square test shows that both sections are significantly active texts; (2) the u -test and nonparametric two-related-sample test show that the two texts do not differ from each other significantly either holistically or by the 300-character segments in terms of activity and descriptivity; and (3) the activity sequences (Q -sequence) in the two sections can be both better fitted by two different functions, viz. the beta-function and the Morse function. Moreover, with the development of the text, a synergic relationship is found in the distribution of verbs and adjectives, indicative of a dynamic and complex self-regulating process of the text development. To conclude, contrary to the claim of prior studies that they were written by different authors, our stylometric study has quantitatively demonstrated that Daojing and Dejing are not independent of each other stylistically, especially in terms of activity and descriptivity.